Elderly Who Care for Elderly: DoubleVulnerability and Quality of Life - Flesch, Letícia Decimo; Batistoni, Samila Sathler Tavares; Neri, Anita Liberalesso; Cachioni, Meire (Paidéia (Ribeirão Preto), 2020)
Elderly caregivers of other elderly people suffer from double vulnerability because they must deal with demands for care and for their own health. The objective of this study was to identify the association between double vulnerability and quality of life of elderly caregivers. The 148 participants were evaluated in relation to socio-demographic variables, quality of life, health selfassessment, perceived burden, measures of physical health of the caregiver and physical and cognitive vulnerability of the elderly who is the target of care. The hierarchical multivariate analysis showed that the elderly caregivers with the highest risk of worse quality of life were those with three or more diseases, with medium or high burden and with a worse health evaluation compared to the past. Greater health weakness is expected over the course of ageing; therefore, to study elderly caregivers, the perception of changes in health is a more pertinent measure than just the assessment of immediate health.